Theoretical modeling and experimental investigation on a novel screwed-type piezoelectric focusing mechanism for space cameras. (15th May 2022) - Jia, Botao; Wang, Liang; Wang, Ruifeng; Jin, Jiamei; Wu, Dawei
Highlights: A novel piezoelectric focusing mechanism is proposed in this article. A general TMM model is created to reveal dynamic behaviors of the proposed stator. The proposed screwed-type piezoelectric actuator can adapt to the space environment. Abstract: Traditional focusing mechanisms for space cameras are driven by a stepper motor with transmission parts, holding the disadvantages of complex structure, low space utilization, electromagnetic interference, and difficulty in self-locking. In order to overcome the above defects, a novel screwed-type piezoelectric focusing mechanism is proposed for space cameras. A screwed-type piezoelectric actuator with a hollow tube stator and rotor is proposed to directly drive a focusing lens to achieve a variation in the focal length. The stator with internal thread operates with two orthogonal bending vibrations and drives the rotor with thread to achieve linear motion by friction. An axial pre-pressure adjustment structure is designed to improve the output performance of the screwed-type piezoelectric actuator in a weightless environment. In order to reveal the dynamic characteristics of the stator and to determine its physical dimensions, an electromechanical coupling model is created using the transfer matrix method. A prototype of the stator is fabricated, and its vibration characteristics were tested to confirm the correctness of the developed theoretical model. In addition, the mechanical output characteristics of the screwed-type piezoelectric actuator prototype are experimentally evaluated. The experimental results shown that: 1. The maximum axial load weight to actuator weight ratio reaches 4.8 under peak-to-peak excitation voltages of 100 Vp-p ; and 2. the actuator prototype can operate in high-temperature (100 °C) and high-vacuum (1.5 × 10 -3 Pa) environments. Finally, the feasibility of the screwed-type piezoelectric focusing mechanism is experimentally demonstrated. The minimum displacement resolution of the mechanism prototype reaches 5.01 μm when the duty ratio is 1.20%, and the mechanism focuses on the image located at 3300 mm. The proposed piezoelectric focusing mechanism can realize high-precision linear positioning without transmission parts, and can realize self-locking without power, presenting the potential application in space cameras.